2017
DOI: 10.1186/s12969-016-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of rheumatic in-patient diagnoses at a pediatric hospital in Kenya

Abstract: BackgroundPediatric rheumatic diseases are chronic illnesses that can cause considerable disease burden to children and their families. There is limited epidemiologic data on these diseases in East Africa. The aim of this study was to assess the spectrum of pediatric rheumatic diagnoses in an in-patient setting and determine the accuracy of ICD-10 codes in identifying these conditions.MethodsMedical records from Gertrude’s Children’s Hospital in Kenya were reviewed for patients diagnosed with “diseases of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
3
13
0
2
Order By: Relevance
“…Kawasaki disease, Takayasu arteritis and IgA vasculitis were observed in this study, our findings which are consistent with reports from India, South Africa and Kenya and demonstrate existence of these rare rheumatic disorder in Tanzania [7,13,16,26]. Kawasaki disease has been previously described from Tanzania in a case report by Noorani et al [11] Interesting Olaosebikan et al did not find any case of vasculitis in a study conducted in Nigeria [8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Kawasaki disease, Takayasu arteritis and IgA vasculitis were observed in this study, our findings which are consistent with reports from India, South Africa and Kenya and demonstrate existence of these rare rheumatic disorder in Tanzania [7,13,16,26]. Kawasaki disease has been previously described from Tanzania in a case report by Noorani et al [11] Interesting Olaosebikan et al did not find any case of vasculitis in a study conducted in Nigeria [8].…”
Section: Discussionsupporting
confidence: 91%
“…Predominance of female children was observed in our study, this is like report by Olaosebikan et al from Nigeria, this similarity is partly attributed to the predominant rheumatic disorders note in the two reports whereby juvenile idiopathic arthritis was the most frequent condition [8]. Migowa et al and Patra et al reported predominance of male children in their reports, of interest is the fact that Patra et al observed predominance of JIA as was a case for our findings, while Migowa et al did not document JIA [7,13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Prevalence of PRDs referred to the childhood rheumatology clinic was 57.8% and 2.8% reported in Singapore and Nigeria respectively [3,21]. Migowa A et al, reported PRDs in 0.32% of hospital admitted cases in Kenya in 2011 [10]. In our study, a total of 43 cases with MSK complaint attending the pediatric rheumatology clinic were reviewed, among which 37 cases (86%) were diagnosed as PRDs (Table 2).…”
Section: Discussionmentioning
confidence: 59%
“…In developing countries, difficult estimation of PRDs prevalence is usually related to decreased awareness of physicians towards rheumatic diseases in children, lack of pediatric rheumatology service and directed attention towards the communicable diseases in comparison to non-communicable rheumatic disorders [6][7][8]. The confusing presentation of musculoskeletal (MSK) symptoms -which are the primary features of rheumatic diseases -in other systemic disorders as metabolic, endocrine, neoplastic and infectious conditions is considered related too [3,[9][10]. Yemen is a developing country; thorough web search did not reveal any published PRDs registry in Yemen.…”
Section: Introductionmentioning
confidence: 99%